Compressive Strength Development and Homogeneity of Concrete Incorporating Fly Ash and Used Engine Oil as Chemical Admixture - Saad S.A.; Jamaluddin A.N.; Masjuki S.A.; Husain N.M.; Hassan W.N.F.W.; Azahar W.N.A.W.; Kasim N.; Beddu S. (Springer Science and Business Media Deutschland GmbH, 2025)
In this paper, the hardened properties of concrete with the utilization of waste materials of pulverized fly ash (PFA) and used engine oil (UEO) as chemical admixtures are conducted in order to improve concrete properties in terms of its compressive strength development and its homogeneity. Ordinary Portland cement (OPC) is replaced by PFA at the percentage of 20% and 40%, respectively. Meanwhile, UEO is added by the dosage of 0.15 and 0.3%, subsequently. Slump test was done for determination of rheological properties of fresh concrete. Compression test and ultrasonic pulse velocity (UPV) test are conducted to analyze the mechanical properties of hardened concrete and its homogeneity. Based on the non-destructive test, UPV test recorded the highest value with concrete sample of 20% PFA and 0.3% UEO of 4.19km/s at 28days, which demonstrate a high integrity of a concrete. For a destructive test, it also follows the same trend having concrete sample of 20% PFA and 0.3% UEO recorded the highest compressive strength which was at 42.74MPa at 90days. It can be concluded that, utilization of these waste materials improves properties of fresh concrete without much adverse effect on properties of hardened concrete. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.